2021
DOI: 10.1590/1519-6984.223633
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock mediates transcriptional regulation of citrulline metabolism in grafted watermelon

Abstract: Citrulline is a non-essential amino acid, involved in key biological functions in plants and humans. Rootstocks have a major impact on citrulline accumulation in grafted watermelon. Information regarding rootstock induced changes in citrulline metabolism is elusive. To understand the regulatory mechanism, parallel changes in the expression profiles of citrulline metabolic genes and citrulline content of watermelon were monitored during the development of self-rooted watermelon and watermelon grafted onto pumpk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
(83 reference statements)
1
4
1
Order By: Relevance
“…In studies done with 14 and 56 watermelon cultivars, no correlation was found with watermelon type (e.g., open-pollinated and hybrid cultivars) and citrulline content (Rimando and Perkins-Veazie, 2005;Kyriacou et al, 2018). Results have been inconclusive regarding citrulline content and watermelon grafting as some rootstockscion combinations have been shown to increase citrulline content (Davis et al, 2008) or have no effect with grafting (Aslam et al, 2020). In our study, citrulline did not change substantially either with grafting or hollow heart ( Table 2).…”
Section: Sugar and Phytonutrient Composition In Grafted Watermelon Wicontrasting
confidence: 72%
“…In studies done with 14 and 56 watermelon cultivars, no correlation was found with watermelon type (e.g., open-pollinated and hybrid cultivars) and citrulline content (Rimando and Perkins-Veazie, 2005;Kyriacou et al, 2018). Results have been inconclusive regarding citrulline content and watermelon grafting as some rootstockscion combinations have been shown to increase citrulline content (Davis et al, 2008) or have no effect with grafting (Aslam et al, 2020). In our study, citrulline did not change substantially either with grafting or hollow heart ( Table 2).…”
Section: Sugar and Phytonutrient Composition In Grafted Watermelon Wicontrasting
confidence: 72%
“…It also found that grafting also affected rootstock rhizosphere microbiome assembly, the scion genotype highly influences the rootstock microbiome in Rosa sp [25]. These results were also found in other tropical crops, such as rubber tree [26] and watermelon [5].…”
Section: Discussionmentioning
confidence: 58%
“…Selection of rootstock and scion is the top priority in fruit tree grafting because differential responses between rootstock and scion [4]. This is because rootstock mediates transcriptional regulation and accumulation of secondary metabolites [5,6]. Furthermore, grafting also affect endogenous hormones contents [7] and oxidative defense reaction [8], even enhance resistance to biotic and abiotic stresses [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The selection of rootstock and scion is the top priority in fruit tree grafting because of the differential responses between rootstock and scion in this process [ 4 ]. This is because rootstock mediates transcriptional regulation and the accumulation of secondary metabolites [ 5 , 6 ]. Furthermore, grafting also affects endogenous hormone content [ 7 ] and oxidative defense reactions [ 8 ], and can even enhance resistance to biotic and abiotic stresses [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%